(untitled) (International Journal of Engineering and Computer Science, 2017)
The past decade saw machine-to-people connections via Internet and people-to- people connections via social networks capturing the world, catapulting it into an era of accessibility and connectivity. Today, the concept has been cranked up into the Internet of ‗Everything‘ that leverages this accessibility and connectivity to efficient and productive use like the smart cities, smart governments and policing, smart grids, smart Transportation and so on. So, the availability of hyper-connectivity sets the stage for building utility and enterprise services around it, which otherwise stay unharnessed. These people-to-machine, people-to-people, machine-to-people and machine-to-machine connections that engage people, processes, data and machines in a bidirectional flow of information results in enormous amount of data which needs to be stored, processed and accessed. Such use cases require convergence of machine-to-machine connectivity, event stream processing, Big Data, analytics, Cloud, and mobile technologies. This paper highlights the introduction, standards, bodies and challenges of IoT